2020
DOI: 10.1021/acs.chemmater.0c02929
|View full text |Cite
|
Sign up to set email alerts
|

α-Li2ZnGeS4: A Wide-Bandgap Diamond-like Semiconductor with Excellent Balance between Laser-Induced Damage Threshold and Second Harmonic Generation Response

Abstract: Exploring new nonlinear optical (NLO) materials with high laser-induced damage threshold (LIDT) in the infrared (IR) region is vital for the development of technologies relying on tunable laser systems. Herein, we report on a quaternary diamond-like semiconductor, α-Li2ZnGeS4, crystallizing in the polar, noncentrosymmetric orthorhombic space group Pna21. The wide optical bandgap of 4.07 eV prohibits multiphoton absorption, concurrently yielding an impressive LIDT around 61.5× that of the benchmark NLO material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
83
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 68 publications
7
83
0
Order By: Relevance
“…[13] To achieve this point, al arge number of DLS IR NLO materials have been developed, and most of them are mainly composed of univalent alkali metal or IB group metal tetrahedra M I Q 4 (M I = Li, Cu, Ag;Q= S, Se) with IIB,I IIA and IVAg roup element tetrahedra MQ 4 (M = Zn, Cd, Hg, Al, Ga, In, Si, Ge, and Sn). [14] Based on the study of composition-structureproperty relations,i tw as shown that the alkali metal tetrahedra can produce larger band gap than the transition metal tetrahedra, while the IIB,IIIA and IVAgroup element tetrahedra are usually applied as the NLO active units to generate large SHG response in the compounds. [15] It is worth noting that, similar to the alkali metals,t he alkaline-earth metals (AEMs) without d-d or f-f electronic transitions are also agood choice to widen the band gap of materials,which has been demonstrated in the non-DLS compounds like Na 2 BaGeS 4 (3.70 eV), [16] Li 2 BaGeS 4 (3.66 eV), [17] BaGa 4 S 7 (3.54 eV), [18] BaGa 2 SiS 6 (3.75 eV) [19] and BaB 2 S 4 (3.61 eV).…”
Section: Introductionmentioning
confidence: 99%
“…[13] To achieve this point, al arge number of DLS IR NLO materials have been developed, and most of them are mainly composed of univalent alkali metal or IB group metal tetrahedra M I Q 4 (M I = Li, Cu, Ag;Q= S, Se) with IIB,I IIA and IVAg roup element tetrahedra MQ 4 (M = Zn, Cd, Hg, Al, Ga, In, Si, Ge, and Sn). [14] Based on the study of composition-structureproperty relations,i tw as shown that the alkali metal tetrahedra can produce larger band gap than the transition metal tetrahedra, while the IIB,IIIA and IVAgroup element tetrahedra are usually applied as the NLO active units to generate large SHG response in the compounds. [15] It is worth noting that, similar to the alkali metals,t he alkaline-earth metals (AEMs) without d-d or f-f electronic transitions are also agood choice to widen the band gap of materials,which has been demonstrated in the non-DLS compounds like Na 2 BaGeS 4 (3.70 eV), [16] Li 2 BaGeS 4 (3.66 eV), [17] BaGa 4 S 7 (3.54 eV), [18] BaGa 2 SiS 6 (3.75 eV) [19] and BaB 2 S 4 (3.61 eV).…”
Section: Introductionmentioning
confidence: 99%
“…[13] To achieve this point, al arge number of DLS IR NLO materials have been developed, and most of them are mainly composed of univalent alkali metal or IB group metal tetrahedra M I Q 4 (M I = Li, Cu, Ag;Q= S, Se) with IIB,I IIA and IVAg roup element tetrahedra MQ 4 (M = Zn, Cd, Hg, Al, Ga, In, Si, Ge, and Sn). [14] Based on the study of composition-structureproperty relations,i tw as shown that the alkali metal tetrahedra can produce larger band gap than the transition metal tetrahedra, while the IIB,IIIA and IVAgroup element tetrahedra are usually applied as the NLO active units to generate large SHG response in the compounds. [15] It is worth noting that, similar to the alkali metals,t he alkaline-earth metals (AEMs) without d-d or f-f electronic transitions are also agood choice to widen the band gap of materials,which has been demonstrated in the non-DLS compounds like Na 2 BaGeS 4 (3.70 eV), [16] Li 2 BaGeS 4 (3.66 eV), [17] BaGa 4 S 7 (3.54 eV), [18] BaGa 2 SiS 6 (3.75 eV) [19] and BaB 2 S 4 (3.61 eV).…”
Section: Introductionmentioning
confidence: 99%
“…While majority of La 6 (TM) x Si 2 S 14 phases studied here show no phase matching, La 6 Cu 2 Ge 2 S 14 exhibits not only phase matchability but also SHG values comparable to the AgGaS 2 standard (Table S7 † ). The obtained non-linear optical properties are comparable to other TM-free studied analogues in this family, ×0.5–1.8 SHG and ×2.5–6 LDT as compared to those for AgGaS 2 : La 6 Li 2 Ge 2 S 14 , La 6 Li 2 Sn 2 S 14 , 56 Sm 6 Li 2 Si 2 S 14 , 28 La 6 Sb 0.66 Si 2 S 14 , 14 La 6 Ga 2 GeS 14 , 27 and La 6 In 2 GeS 14 ; 27 as well as other sulfides (Li 2 ZnGeS 4 , 95 Li 2 MnGeS 4 , 96 Na 2 Hg 3 M 2 S 8 (ref. 97 )) and pnictides (RuSi 4 P 4 and IrSi 3 P 3 , 9 MgSiAs 2 , 98 Ba 2 Si 3 P 6 , 99 and MnSiP 2 (ref.…”
Section: Resultsmentioning
confidence: 99%